2021
DOI: 10.3390/ani11102977
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Pathways Associated with Feed Efficiency and Meat Quality Traits in Slow-Growing Chickens

Abstract: Here, molecular pathways and genes involved in the feed efficiency (FE) and thigh-meat quality of slow-growing Korat chickens were investigated. Individual feed intake values and body weights were collected weekly to the calculate feed conversion ratios (FCR) and residual feed intake. The biochemical composition and meat quality parameters were also measured. On the basis of extreme FCR values at 10 weeks of age, 9 and 12 birds from the high and the low FCR groups, respectively, were selected, and their transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…However, the FE trait is a complex phenotype that can be difficult to assess as compared with other traits [ 33 ]. Some signaling pathways have been related to FE, but very few candidate genes have been identified [ 34 , 35 , 36 ]. One possible explanation for this lack of knowledge is that FE is a complicated economic trait that may be controlled by many different genes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the FE trait is a complex phenotype that can be difficult to assess as compared with other traits [ 33 ]. Some signaling pathways have been related to FE, but very few candidate genes have been identified [ 34 , 35 , 36 ]. One possible explanation for this lack of knowledge is that FE is a complicated economic trait that may be controlled by many different genes.…”
Section: Discussionmentioning
confidence: 99%
“…These groups are later referred to as the low-FE and high-FE groups, respectively. The studied birds were the same as in our previous gene expression study of the KR thigh muscle ( Poompramun et al, 2021a ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous skeletal muscle transcriptomic analysis in chicken has indicated that FE may be related to nucleotide sugar biosynthesis, glycogen metabolism, and lipid uptake and transport ( Abasht et al, 2019 ). Our previous transcriptomic analysis with KR chicken indicated that nucleotide metabolism, fatty acid metabolic process, and oxidative stress play key roles in regulating both FE and the quality of thigh meat ( Poompramun et al, 2021a ). Thus, improving FE can have a negative impact on meat texture and the nutritional value of meat via activating the accumulation of biochemical compounds and flavor precursors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, animals with similar body weights (BWs) always required rather widely different amounts of feedstuff for similar body weight gain (BWG) (Yi et al, 2018 ). Moreover, the accurate calculation of the nutritional requirement of growing animals was far beyond the directed ratio calculation between the feed intake (FI) and BWG (Kelly et al, 2019 ; Poompramun et al, 2021a ). Therefore, the residual feed intake (RFI), which indicates the discrepancy between the actual and the predicted FI based on the body size and growth rate of animals, was applied to improve the animal FE (Bezerra et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%